Apical pulmonary lesions suspected of malignancy visible on neck CT angiography performed for acute stroke: Prevalence, treatment, and clinical implications – the PLEURA study. (June 2023) - Dittrich, Tolga D; Aujesky, Mara; Rudin, Salome; Zietz, Annaelle; Wagner, Benjamin; Polymeris, Alexandros; Altersberger, Valerian L; Sinnecker, Tim; Gensicke, Henrik; Engelter, Stefan T; Lyrer, Philippe; Hess, Viviane; et al.
Background: Computed tomography angiography (CTA) of the supraaortic arteries is commonly used for acute stroke workup and may reveal apical pulmonary lesions (APL). Aim: To determine the prevalence, follow-up algorithms, and in-hospital outcomes of stroke patients with APL on CTA. Methods: We retrospectively included consecutive adult patients with ischemic stroke, transient ischemic attack, or intracerebral hemorrhage and available CTA at a tertiary hospital between January 2014 and May 2021. We reviewed all CTA reports for the presence of APL. APL were classified as malignancy suspicious or benign appearing based on radiological-morphological criteria. We performed regression analyses to investigate the impact of malignancy suspicious APL on different in-hospital outcome parameters. Results: Among 2715 patients, APL on CTA were found in 161 patients (5.9% [95%CI: 5.1–6.9]; 161/2715). Suspicion of malignancy was present in one third of patients with APL (36.0% [95%CI: 29.0–43.7]; 58/161), 42 of whom (72.4% [95%CI: 60.0–82.2]; 42/58) had no history of lung cancer or metastases. When performed, further investigations confirmed primary or secondary pulmonary malignancy in three-quarters (75.0% [95%CI: 50.5–89.8]; 12/16), with two patients (16.7% [95%CI: 4.7–44.8]; 2/12) receiving de novo oncologic therapy. In multivariable regression, the presence of radiologically malignancy suspicious APL was associated with higher NIHSS scores at 24 h (beta = 0.67, 95%CI: 0.28–1.06, p  = 0.001) and all-cause in-hospital mortality (aOR = 3.83, 95%CI: 1.29–9.94, p  = 0.01). Conclusions: One in seventeen patients shows APL on CTA, of which one-third is malignancy suspicious. Further work-up confirmed pulmonary malignancy in a substantial number of patients triggering potentially life-saving oncologic therapy.